2014
DOI: 10.1007/s00705-014-2080-9
|View full text |Cite
|
Sign up to set email alerts
|

Complete genomic sequence of the coronavirus transmissible gastroenteritis virus SHXB isolated in China

Abstract: A strain of transmissible gastroenteritis virus (TGEV), SHXB, was isolated in Shanghai, China. The complete genome of strain SHXB was sequenced, and its sequence was compared those of other TGEV strains in the GenBank database. The comparison showed that there were no insertions or deletions in the 5' and 3'- non-translated regions, in the nonstructural genes ORF1, ORF3, and ORF7, or in the genes encoding the structural proteins envelope (E), membrane (M) and nucleoprotein (N). A phenomenon in common with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…CH‐SY and CH‐ZB were closely correlated with Miller M6, which is a virulent TGEV strain, while CH‐SH was correlated with Miller M60, which is an attenuated TGEV strain. Previous reports showed that the Purdue cluster also occurred in China (Weiwei et al., ). The current results thus indicate that the Miller, as well as the Purdue cluster, exists in Chinese field strains of TGEV.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…CH‐SY and CH‐ZB were closely correlated with Miller M6, which is a virulent TGEV strain, while CH‐SH was correlated with Miller M60, which is an attenuated TGEV strain. Previous reports showed that the Purdue cluster also occurred in China (Weiwei et al., ). The current results thus indicate that the Miller, as well as the Purdue cluster, exists in Chinese field strains of TGEV.…”
Section: Resultsmentioning
confidence: 92%
“…Transmissible gastroenteritis virus is currently divided into two distinct genogroups: the Miller cluster and the Purdue cluster (Hu et al., ). Transmissible gastroenteritis virus occurs in suckling piglets in swine‐producing areas in China (Weiwei et al., ). The TGEV genome was first sequenced by the analysis of polymerase chain reaction (PCR) products in 1993 (Chen, Pocock, & Britton, ).…”
Section: Introductionmentioning
confidence: 99%
“…Transmissible gastroenteritis virus (strain SHXB) was isolated in Shanghai, China. The complete genome sequence for TGEV SHXB is available in GenBank (KP202848.1) (Weiwei et al, 2014). To analyze viral entry, cells were incubated with TGEV at a multiplicity of infection of 2 (MOI = 2) for 1 h at 4°C.…”
Section: Virus Infection and Assaysmentioning
confidence: 99%
“…TGEV strain SHXB was isolated in Shanghai, China. The complete genome sequence for this virus is available at the GenBank database (ID number: KP202848.1) [13]. For experimental assays, cells were incubated with TGEV at a multiplicity of infection (MOI) of 2 for 1 h at 4˚C in serum-free medium and washed with phosphate-buffered saline (PBS; pH 7.2) at 4˚C three times to remove unbound virus.…”
Section: Viral Infectionmentioning
confidence: 99%